Critical Learning in the on-line classroom: An action learning approach to instructor development - Goumaa, Rasha; Hay, Amanda (Proceedings of the International Conference on Networked Learning, 2018)
Teaching in an online classroom is often new to university teachers which highlights the importance of training and development for faculty in on-line instruction in order to realise the promise of this burgeoning form of delivery. However, current research that examines formal training initiatives offered by universities tends to promote an ‘instrumental’ understanding of online facilitation and teaching. We argue that this promotes a narrow and mechanistic view, reducing successful online teaching to the mere acquisition of a set of technical competencies alongside the mastery of theoretical concepts and models of online learning. Networked learning which emphasises relational and interactional aspects of the online classroom, suggests that it is also important to recognize that teachers play a core role in helping students on their journeys to becoming critically reflective practitioners. From this perspective, facilitating learning in an online environment is not an emotion and value free task for which a set of skills can be easily learnt and later applied. Instead, it suggests the importance of dialogical approaches which pay attention to issues of power, voice, access and inclusion as well as the emotional dynamics which pervade the classroom. This then, unlike dominant forms of university training initiatives, depicts online teaching as a practice with its own ethical values and problematic issues in supporting online students’ critical learning. While the argument that teaching online requires changes to conventional teaching approaches is not new, there is a dearth of research on instructors’ perspectives on promoting critical learning in classroom relational dialogue. Against this background, and recognising the challenges of advancing critical pedagogies in general, this proposal explores the novel use of an action learning approach to online instructor development in the context of two management education programmes. Action learning, by emphasising learning by doing, represents one of the most commonly used forms of experiential learning. We suggest that the use of action learning sets offers novice instructors the opportunity to consider frequently taken-for-granted aspects of their practice such as the emotions and politics so crucial to promoting critical forms of learning and so facilitating students’ journeys towards becoming critically reflective practitioners.